Topical Sustained Delivery of Miltefosine Via Drug-Eluting Contact Lenses to Treat Acanthamoeba Keratitis - Lin Chen; Liangju Kuang; Amy E. Ross; Wissam Farhat; Nikolay Boychev; Sina Sharfi; Levi N. Kanu; Longqian Liu; Daniel S. Kohane; Joseph B. Ciolino (MDPI AG, 2022)
This study aimed to develop a miltefosine-eluting contact lens (MLF-CL) device that would allow sustained and localized miltefosine release for the treatment of Acanthamoeba keratitis. MLF-CLs were produced in three different miltefosine doses by solvent-casting a thin miltefosine-polymer film around the periphery of a methafilcon hydrogel, which was then lathed into a contact lens. During seven days of in vitro testing, all three formulations demonstrated sustained release from the lens at theoretically therapeutic levels. Based on the physicochemical characterization of MLF-CLs, MLF-CL's physical properties are not significantly different from commercial contact lenses in terms of light transmittance, water content and wettability. MLF-CLs possessed a slight reduction in compression modulus that was attributed to the inclusion of polymer-drug films but still remain within the optimal range of soft contact lenses. In cytotoxicity studies, MLF-CL indicated up to 91% viability, which decreased proportionally as miltefosine loading increased. A three-day biocompatibility test on New Zealand White rabbits revealed no impact of MLF-CLs on the corneal tissue. The MLF-CLs provided sustained in vitro release of miltefosine for a week while maintaining comparable physical features to a commercial contact lens. MLF-CL has a promising potential to be used as a successful treatment method for Acanthamoeba keratitis.